DETEKSI DINI KEHAMILAN BERISIKO DENGAN KARTU SKOR POEDJI ROCHJATI (KSPR) DI PUSKESMAS MEDAN DELI TAHUN 2024 - Hedy Tan; Hotmauli Sitanggang; Tria Amelia Putri Saragih (Jurnal Ilmiah Kebidanan Imelda, 2025)
Introduction: Risky pregnancies can cause serious complications for the mother and fetus, such as bleeding, preeclampsia and maternal death. Early detection using KSPR is very important to identify pregnant women at high risk and provide appropriate intervention. Objective: This study aims to detect early risk pregnancies using the Poedji Rochjati Score Card (KSPR) at the Medan Deli Community Health Center in 2024. Method: This research method is descriptive quantitative with data collection through interviews and observations on 114 pregnant women. The sampling technique used in this study was total sampling. The study ran from May to August 2024. Results: The results showed that 38% of pregnant women were at high risk, with the main risk factors including maternal age over 35 years, pregnancies too close together, and a history of previous risky pregnancies. Conclusion: The use of the KSPR has proven to be beneficial in categorizing pregnancy risk levels practically and quickly. This aligns with the initial goal of developing the KSPR by Poedji Rochjati: as a simple screening tool in primary care to support efforts to reduce maternal mortality (MMR) and infant mortality (IMR). With consistent use of the KSPR, health workers can more easily determine midwifery care plans, educate families, and prepare referrals when needed.